2002
DOI: 10.2174/0929867023369998
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Prodrugs

Abstract: Bisphosphonates (BP) are pyrophosphate analogs having a P-C-P backbone. The oral bioavailability of BPs is ca. 1%, due to high ionisation at physiological pH. Using the prodrug approach, oral absorption can be increased by masking one or more ionizable groups (clodronate, etidronate), or using a targeting carrier system (alendronate, pamitronate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…On the other hand, structure-activity relationship (SAR) studies of bisphosphonates have demonstrated that nitrogen-containing bisphosphonates are more potent inhibitors of bone resorption, and furthermore, introduction of a cyclic group on the side chain may increase the anti-resorptive potency. 7 Therefore, we designed and synthesized a new type of bisphosphonates with various aromatic rings on the side chains linked by amide bonds (Fig. 2).…”
mentioning
confidence: 99%
“…On the other hand, structure-activity relationship (SAR) studies of bisphosphonates have demonstrated that nitrogen-containing bisphosphonates are more potent inhibitors of bone resorption, and furthermore, introduction of a cyclic group on the side chain may increase the anti-resorptive potency. 7 Therefore, we designed and synthesized a new type of bisphosphonates with various aromatic rings on the side chains linked by amide bonds (Fig. 2).…”
mentioning
confidence: 99%
“…Indeed, they lack the acid features, although compounds 1aef could act as prodrugs with subsequent ester cleavage. Other attempts to synthesized BPs prodrugs have been proposed [25] suggesting that several groups (such as carboxylic esters, amides, anhydrides) can be used to functionalize the acid phosphate in order to improve the compound's oral bioavailability. The presence of the indole scaffold and the esterification of the bisphosphonate moiety also results in a significant increase of the LogP value.…”
Section: Tablementioning
confidence: 99%
“…For related literature, see: Barbey et al (2003), Migianu et al (2005), Fleisch (1998Fleisch ( , 2002; Clezardin et al (2003); Green & Clezardin (2002); Lecouvey et al (2003a,b); Vepsalainen (2002 Table 1 Hydrogen-bond geometry (Å , ). Symmetry codes: (i) x; y þ 1; z; (ii) Àx þ 1; Ày; Àz; (iii) x; y À 1; z; (iv) x þ 1; y; z.…”
Section: Related Literaturementioning
confidence: 99%
“…Moreover, they induce some secondary effects such as gastric and intestinal problems and osteonecrosis of the jaw-bone. To circumvent to these drawbacks, a prodrug strategy was considered that would deliver bisphosphonates with an improved gastrointestinal absorption (Vepsalainen, 2002). The approach in our laboratory consists of modifying the phosphonic acid functionality itself, by introducing an ester group (Lecouvey et al, 2003a,b).…”
Section: S1 Commentmentioning
confidence: 99%